ته‌كنیكی نیگاركێشانی دیجیتاڵی له‌ نێو هونه‌ری كاریكاتێردا - فتاح, سام احمد (Sulaimani Journal for Humanities, 2021)
This is research is a descriptive - Analytical research on “ the techniques of digital paintings in caricature art” currently, as one of the influential and creative artistic media in the field of visual art. The first section of the research is devoted to illustrate the research problem, it’s importance, goal, and the limitations of (time and place), then defining the most important terms. The aim of this research is to show and define the features, technical characteristics, and digital painting tools that led to the depiction and embodiment of the caricature works. The second section in the first topic: As part of the theoretical framework of the research, it deals with the historical origins of the art of caricature and its’ types. And the second section: The second topic: Deals with the techniques and tools of digital caricature drawing, related to the relationship between the traditional drawing and digital drawing and the difference between them, with tools, programs, and digital caricature techniques. Section Three: Research Procedures: 1-The Research Community, 2-The Research Sample, 3-The Research Tool, 4-Collecting Information Tool, 5- The Research Methods. Section Four: is for the results and conclusions.